Factors affecting gross efficiency in cycling - de Koning, J. J.; Noordhof, D. A.; Lucia, A.; Foster, C. (International Journal of Sports Medicine, 2012)
There is little standardization of how to measure cycling gross efficiency (GE). Therefore, the purposes of these studies were to evaluate the effect of: i) stage duration, ii) relative exercise intensity, iii) work capacity and iv) a prior maximal incremental test on GE. Trained subjects (n=28) performed incremental tests with stage durations of 1-, 3-, and 6-min to establish the effect of stage duration and relative exercise intensity on GE. The effect of work capacity was evaluated by correlating GE with peak power output (PPO). In different subjects (n=9), GE was measured at 50% PPO with and without a prior maximal incremental test. GE was similar in 3- and 6-min stages (19.7±2.8% and 19.3±2.0%), but significantly higher during 1-min stages (21.1±2.7%), GE increased with relative exercise intensity, up to 50% PPO or the power output corresponding to the ventilatory threshold and then remained stable. No relationship between work capacity and GE was found. Prior maximal exercise had a small effect on GE measures; GE was lower after maximal exercise. In conclusion, GE can be determined robustly so long as steady state exercise is performed and RER </= 1.0.